HUBUNGAN FAKTOR SOSIAL EKONOMI PETANI PADI DENGAN PELAKSANAAN PENERAPAN PENGELOLAAN TANAMAN TERPADU (PTT) DI KELURAHAN GALUNG KECAMATAN TAPALANG KABUPATEN MAMUJU - Nurhaedah Nurhaedah; Rasdah Rasdah; Irmayani Irmayani (Jurnal Saintifik (Multi Science Journal), 2023)
The aim of the study was to determine the relationship between the socio-economic factors of rice farmers and the application of Integrated Crop Management (PTT) in Galung Village, Tapalang District, Mamuju Regency. This type of research is qualitative research based on primary and secondary data in the field. Based on the results of data analysis research conducted in Galung Village, Tapalang District, Mamuju Regency and the discussion that has been put forward, the following conclusions are obtained: 1. Based on the results of the analysis and discussion that the variable capital (X1), quality seeds, (X2) planting system, ( X3) balanced fertilization, (X4) control of weeds, pests and plant diseases, (X5) harvest and post-harvest and (Y) simultaneously have a significant and positive effect on the income level of farmers in the District. 2. The variables of capital, land area, and technology partially have a significant and positive relationship to the income of farmers in Galung Village, Tapalang District, Mamuju Regency.